Anticoagulation with dabigatran does not increase secondary intracerebral haemorrhage after thrombolysis in experimental cerebral ischaemia - Sun, Li; Zhou, Wei; Ploen, Robert; Zorn, Markus; Veltkamp, Roland (Thrombosis and haemostasis, 2013)
Dabigatran etexilate (DE) has recently been introduced for stroke prevention in atrial fibrillation, but management of acute ischaemic stroke during therapy with DE is a challenge. Thrombolysis is contrain-dicated because of a presumed increased risk of intracerebral haemorrhagic complications. We studied in different ischaemia models whether DE increases secondary haemorrhage after thrombolysis. C57BL/6 mice were anticoagulated with high-dose DE or warfarin. After 2 hour (h) or 3 h transient filament MCAO, rt-PA was injected. At 24 h after MCAO, secondary haemorrhage was quantified using a macroscopic haemorrhage score and haemoglobin spectrophotometry. Post-ischaemic blood-brain-barrier (BBB) damage was assessed using Evans blue. To increase the validity of findings, the duration of anticoagulation was prolonged in mice (5 x DE over 2 days), and the effect of DE after thrombolysis was also examined in thromboembolic MCAO in rats. Pretreatment with warfarin resulted in significantly more secondary haemorrhage (mean haemorrhage score 2.6 ± 0.2) compared to non-anticoagulated animals (1.7 ± 0.3) and DE (9 mg/kg, 1.6 ± 0.3) in 2 h ischaemia. Also after a 3 h period of ischaemia, haemorrhage was more severe in animals anticoagulated with warfarin compared to 9 mg/kg DE and non-anticoagulated control. Prolonged or enteral dabigatran pretreatment led to identical results. Also, thrombolysis after thromboembolic MCAO in rats did not induce more severe bleeding in DE-treated animals. Mice pretreated with warfarin had higher BBB permeability and increased activation of matrix-metalloproteinase 9. In conclusion, DE does not increase the risk of secondary haemorrhage after thrombolysis in various rodent models of ischaemia and reperfusion. The implications of this finding for stroke patients have to be determined in the clinical setting.
Publikationsdatum: 30. November 2017 (online)
Eletronische Reproduktion der Druck-Ausgabe
Gesehen am 27.01.2022